Gene expression regulation by upstream open reading frames in rare diseases - Silva, Joana (2018)
Upstream open reading frames (uORFs) constitute a class of cis-acting elements that regulate translation initiation. Mutations or polymorphisms that alter, create or disrupt a uORF have been widely associated with several human disorders, including rare diseases. In this mini-review, we intend to highlight the mechanisms associated with the uORF-mediated translational regulation and describe recent examples of their deregulation in the etiology of human rare diseases. Additionally, we discuss new insights arising from ribosome profiling studies and reporter assays regarding uORF features and their intrinsic role in translational regulation. This type of knowledge is of most importance to design and implement new or improved diagnostic and/or treatment strategies for uORF-related human disorders.